2000
DOI: 10.1002/(sici)1097-0169(200001)45:1<1::aid-cm1>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Molecular responses of human dermal fibroblasts to dual cues: Contact guidance and mechanical load

Abstract: Fibroblast contraction in wound healing involves the interaction of several cell types, cytokines, and extracellular matrix molecules. We have previously developed fibroblast alignment models using precise uniaxial mechanical loads in 3D culture and using contact guidance on fibronectin strands. Our aim here was to use contact guidance to place fibroblasts in their potentially most sensitive configuration, i.e., perpendicular to the axis of loading, to present cells with conflicting guidance cues. Gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
98
1
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(108 citation statements)
references
References 19 publications
(26 reference statements)
8
98
1
1
Order By: Relevance
“…This can lead to spatially directed turnover of the extracellular matrix by directing the osteoclast to a specific location, ultimately resulting in an accurate adaptation of matrix architecture and composition that enables the osteoblasts to better resist mechanical deformation as a result of the forces that act upon them. This theory is supported by findings by Mudera et al, 38 who showed that fibroblasts unable to align to applied loads remodel their matrix far more rapidly than orientated cells.…”
Section: -32supporting
confidence: 60%
“…This can lead to spatially directed turnover of the extracellular matrix by directing the osteoclast to a specific location, ultimately resulting in an accurate adaptation of matrix architecture and composition that enables the osteoblasts to better resist mechanical deformation as a result of the forces that act upon them. This theory is supported by findings by Mudera et al, 38 who showed that fibroblasts unable to align to applied loads remodel their matrix far more rapidly than orientated cells.…”
Section: -32supporting
confidence: 60%
“…The investigators did not examine the cytoskeleton of cells attached to the fibronectin cables, and hence it is unclear whether the cells were responding in any morphological way to the mechanical stimulus. However, the cells on fibronectin exhibited trends in matrix protease gene expression indicative of a mechano-active state 24 .…”
Section: Discussionmentioning
confidence: 99%
“…In another related study, Mudera and co-workers devised a composite matrix of large fibronectin cables embedded in a fibrous collagen gel and oriented perpendicular to the direction of uniaxial mechanical loading 24 . Locally, fibroblasts attached and spontaneously aligned along the fibronectin cables and remained thus during mechanical stimulation, even though neighboring cells in the collagen matrix realigned parallel to the mechanical stimulus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been shown that the extracellular matrix rigidity plays a crucial role in several cellular processes, ranging from locomotion (Lo et al, 2000;Pelham and Wang, 1997), to anchorage dependency of growth control (Burridge and ChrzanowskaWodnicka, 1996;Chen et al, 1997;Folkman and Moscona, 1978), phagocytosis (Beningo and Wang, 2002), differentiation (Cukierman et al, 2001;Deroanne et al, 2001) and ECM remodelling (Mudera et al, 2000;Tranqui and Tracqui, 2000;Urech et al, 2005). Since the rosettes of podosomes are adherent structures, we investigate the influence of the matrix rigidity on the dynamic properties of these structures in 3T3 fibroblasts transfected with GFP-actin.…”
Section: Introductionmentioning
confidence: 99%